FRI0593 A Systematic Literature Review of The Prevalence of Psoriatic Arthritis. (15th July 2016) - Άgh, T.; Vokό, Z.; Heisel, O.; Chiva-Razavi, S.; Barbeau, M.; Szilberhorn, L.; Keown, P.
Abstract : Background: Psoriatic arthritis (PsA) is a heterogeneous multifaceted inflammatory arthritis associated with psoriasis (PsO). PsA causes a substantial disease burden and has a significant societal health impact. Accurately determining the prevalence of PsA can be difficult due to variations in disease presentation over time, changes in disease classification and specialty of the treating physician. Objectives: To perform a systematic literature review of the prevalence of PsA and to identify potential determinants of the prevalence of PsA. Methods: A systematic literature search of English-language articles was conducted in October 2015 using MEDLINE, EMBASE and CINAHL, and was limited to articles published between 2009 and 2015. The systematic literature review was conducted by two independent reviewers in compliance with the PRISMA Statement. Results: Thirty-nine studies (23 clinical studies, 10 database analyses, and 6 population-based surveys) were included. In most of the studies (n=38), the diagnosis of PsA was made by physicians using different classification criteria: Classification Criteria for Psoriatic Arthritis (CASPAR) criteria (n=14), CASPAR and Moll and Wright (M&W) criteria (n=2), CASPAR and Gladman modification of M&W criteria (n=1), CASPAR and Assessment of Spondyloarthritis International Society criteria (n=1), classification criteria for PsA not reported (n=20). In the reviewed articles, only point prevalence rates for PsA were reported. The point prevalence of PsA ranged between 0.02% to 0.67% in the adult population, and 3% to 42% in patients with PsO, with rates differing across countries. PsA seemed to be most prevalent in the 50–59 years age-group. PsA was more common among first-degree relatives of patients with PsA and also showed marked differences between different ethnic groups (showing the highest prevalence in the Caucasian population). The results of studies on gender differences were conflicting: some reported that PsA was more frequent in men and others that it occurred more frequently in women. In the studies reviewed, the majority of PsA patients had peripheral symptoms without axial involvement; polyarthritis seemed to be more prevalent than oligoarthritis. Findings of studies estimating the prevalence of PsA in PsO patients suggested that 29% to 41% of PsO patients attending dermatology clinics had undiagnosed PsA. Conclusions: The high variance of prevalence rates can be explained with the differences in study populations, diagnostic methods and classification criteria of PsA. The prevalence of PsA seemed to be mostly affected by age and genetic factors. Findings of the epidemiological studies measuring the prevalence of PsA in PsO patients suggested that a large proportion of patients with PsO seen in dermatology centers might have PsA that had not been previously diagnosed. Given that untreated PsA may result in irreversible joint damage, increased awareness of this condition among PsO patients may be a critical step in reducing disability in this patient population. Further research is needed to better understand the occurrence of PsA. Disclosure of Interest: T. Άgh Employee of: Syreon Research Institute which received funding for this research from Novartis Pharmaceuticals Canada Inc., Z. Vokό Employee of: Syreon Research Institute which received funding for this research from Novartis Pharmaceuticals Canada Inc., O. Heisel Employee of: Syreon Corporation which received funding for this research from Novartis Pharmaceuticals Canada Inc., S. Chiva-Razavi Employee of: Novartis Pharmaceuticals Canada Inc., M. Barbeau Employee of: Novartis Pharmaceuticals Canada Inc., L. Szilberhorn Employee of: Syreon Research Institute which received funding for this research from Novartis Pharmaceuticals Canada Inc., P. Keown Employee of: Syreon Corporation which received funding for this research from Novartis Pharmaceuticals Canada Inc.